Camphorsulfonate salts of triazolopyrazine derivatives

By developing new camphor sulfonate compounds of triazolopyrazine derivatives, the problems of low storage stability and light stability were solved, and better drug preparation processability and pharmacological activity were achieved.

CN119451965APending Publication Date: 2025-02-14AI BEI & CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380050228.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-05-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The pure substance storage stability and light stability of triazolopyrazine derivatives are low, resulting in poor processability during drug preparation.

Method used

Develop novel camphor sulfonate compounds of triazolopyrazine derivatives to improve their storage stability and photostability.

Benefits of technology

Through the novel camphor sulfonate compound, the storage stability and photostability of triazolopyrazine derivatives are significantly improved, thereby improving the processability and pharmacological activity of drug preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451965A_ABST
    Figure CN119451965A_ABST
Patent Text Reader

Abstract

The present invention relates to a salt of D (+) 10-camphorsulfonic acid and a triazolopyrazine derivative of the following chemical formula 1 (camphorsulfonate), a pharmaceutical composition comprising said salt, a process for the preparation of said salt and the therapeutic use of said salt. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] As is known in the past, triazolopyrazine derivatives are substances useful for treating hyperproliferative diseases by inhibiting the activity of c-Met kinase. However, in existing literature, many of these triazolopyrazine derivatives are proposed in free base form rather than in salt form.

[0002] In order to improve the pharmacological use of the free base form of triazolopyrazine derivatives, a salt form is required. Therefore, the present invention aims to provide a camphorsulfonate salt and a preparation method thereof which maintain the pharmacokinetic and pharmacological activities of the free base form and improve useful physical properties. Background Art

[0003] The present invention relates to a novel camphorsulfonate compound of a triazolopyrazine derivative represented by the following chemical formula 1, a preparation method thereof and a pharmaceutical composition containing the same.

[0004] Chemical formula 1:

[0005]

[0006] The present inventors have found the above-mentioned compound having inhibitory activity against tyrosine kinase, and have made great efforts to research and develop a composition for effectively preventing or treating various hyperproliferative disorders caused by abnormal tyrosine kinase activity. As a result, the present inventors have found that a novel salt compound of the compound of Chemical Formula 1, which has been unknown so far, retains the function of the compound in inhibiting the activity of c-Met kinase and improves the storage stability and photostability of the compound, thereby completing the present invention.

[0007] According to the present invention, the novel camphorsulfonate compound of the compound of Chemical Formula 1 of the present invention activates phosphorylation by binding to hepatocyte growth factor (HGF), thereby significantly inhibiting the activity of c-Met kinase that triggers cell proliferation, migration, and angiogenesis.

[0008] Therefore, the salt compound of the present invention can be usefully used for treating or preventing various abnormal proliferative diseases mediated by excessive angiogenesis activated by abnormal cell proliferation.

[0009] Also, the novel camphorsulfonate salt compound of the compound of Chemical Formula 1 exhibits physical properties different from those of the pure compound, for example, melting point, hygroscopicity, solubility, flow properties or thermodynamic stability.

[0010] Therefore, the salt compound of the compound of Chemical Formula 1 provided by the present invention can be used to select the most suitable form for pharmacological use in the preparation process of medicine or the preparation process of a single pharmaceutical dosage form such as tablets, capsules, ointments, suspensions, or the preparation of a pharmaceutical form with optimal pharmacokinetic properties.

[0011] According to another embodiment of the present invention, the present invention provides a pharmaceutical composition comprising a therapeutically effective amount of the novel camphorsulfonate compound of Chemical Formula 1. For example, the present invention provides a pharmaceutical composition for preventing or treating hyperproliferative disorders, comprising the novel salt compound of the compound of Chemical Formula 1 as an active ingredient.

[0012] In this specification, the term "hyperproliferative disorder" refers to a pathological state caused by excessive cell growth, division and migration in a normally growing animal body that is not regulated by the usual restriction method. Hyperproliferative diseases prevented or treated with the composition of the present invention include, for example, cancer, diabetic retinopathy, retinopathy of prematurity, corneal transplant rejection, neovascular glaucoma, skin erythema, proliferative retinopathy, psoriasis, rheumatoid arthritis, osteoarthritis, autoimmune diseases, Crohn's disease, restenosis, atherosclerosis, intestinal adhesions, ulcers, cirrhosis, glomerulonephritis, diabetic nephropathy, malignant nephrosclerosis, thrombotic microangiopathy, organ transplant rejection and glomerular disorders, but are not limited thereto, including all hyperproliferative diseases caused by abnormal cell proliferation and excessive generation of new blood vessels.

[0013] More preferably, the cancer that is one of the abnormal proliferative diseases that can be prevented or treated with the composition of the present invention is lung cancer, gastric cancer, pancreatic cancer, colorectal cancer, ovarian cancer, renal cell carcinoma, prostate cancer or brain tumor.

[0014] When the composition of the present invention is prepared into a pharmaceutical composition, the pharmaceutical composition of the present invention comprises a pharmaceutically acceptable carrier. The pharmaceutically acceptable carrier contained in the pharmaceutical composition of the present invention is a commonly used carrier during preparation, including lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginate, gelatin, calcium silicate, microcrystalline cellulose, polyvinyl pyrrolidone, cellulose, water, syrup, methylcellulose, methyl hydroxybenzoate, propyl hydroxybenzoate, talc, magnesium stearate and mineral oil, but is not limited thereto. In addition to the ingredients, the pharmaceutical composition of the present invention may also include lubricants, wetting agents, sweeteners, flavor enhancers, emulsifiers, suspending agents, preservatives, etc.

[0015] The pure substance of the triazolopyrazine derivative represented by the above Chemical Formula 1 is not suitable for preparing a general pharmaceutical composition in terms of physical properties such as solubility and thermal stability.

[0016] Therefore, the present inventors screened various salts to develop salt compounds suitable for preparing pharmaceutical dosage forms that improve the solubility and stability of the triazolopyrazine derivatives, thereby developing novel camphorsulfonate compounds that continuously maintain the pharmacological activity of the compounds and have high solubility and excellent stability. Summary of the invention

[0017] Technical issues

[0018] In order to improve the problem of poor processability in drug preparation caused by low storage stability and light stability of the pure substance of the triazolopyrazine derivative represented by the chemical formula 1, the present invention conducts salt screening on the compound, thereby solving the above problem by developing a novel camphorsulfonate compound of the compound.

[0019] Technical Solution

[0020] The present invention can improve the storage stability and light stability of the triazolopyrazine derivative (ABN401) represented by the chemical formula 1 by developing a novel camphosulfonic acid salt (Camsylate) compound of the triazolopyrazine derivative.

[0021] Furthermore, the present invention provides a method for preparing the camphorsulfonate compound and a pharmaceutical composition containing the camphorsulfonate compound as an active ingredient.

[0022] Effects of the Invention

[0023] The present invention relates to a novel camphorsulfonate compound of a triazolopyrazine derivative represented by the chemical formula 1 and a preparation method thereof. The novel camphorsulfonate compound provided by the present invention improves the usefulness and processability of the compound in drug preparation by improving the storage stability and light stability which are problems existing in pure substances.

[0024] The camphorsulfonate compound effectively inhibits the activity of c-Met tyrosine kinase, and can be usefully used as a therapeutic agent for various hyperproliferative diseases associated with excessive cell proliferation and growth due to abnormal kinase activity, such as cancer, psoriasis, rheumatoid arthritis, diabetic retinopathy, etc. In addition, a pharmaceutical composition for inhibiting c-Met tyrosine kinase activity and a pharmaceutical composition for preventing or treating hyperproliferative disorders are provided, which contain the novel salt compound as an active ingredient. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Figure 2 is the temperature profile that occurred in the salt screening experiment of the camphorsulfonate compound.

[0026] Figure 2 is the temperature profile of the isothermal cycle experiment.

[0027] Figure 3 The results of liquid chromatography mass spectrometry using the S19061_03 method with ABN401 as the starting material are shown (retention time = 5.2 min).

[0028] Figure 4 The results of liquid chromatography mass spectrometry using the S19061_01 method and ABN401 as the starting material are shown (retention time = 2.2 min).

[0029] Figure 5 High performance X-ray crystallography (HT-XRPD) patterns of the starting material (Form A), Camp1 and Camp2 are shown.

[0030] Figure 6 Shown are high temperature X-ray crystallography (HT-XRPD) patterns of Camp1 (Exp. ID SSm14) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) for 2 days.

[0031] FIG7 shows TGA (A) and TGMS (B) analysis (heating rate 10° C. / min) of Camp1 (Exp. ID SSm14). It shows a mass loss of 3.3% due to acetone and water at a temperature of 25-120° C. The thermal decomposition of the salt is shown at a temperature of about 240° C., and the heat flow signal analyzed by TGA shows a broad endothermic reaction at a temperature of about 160° C. due to the melting of the anhydride of the salt.

[0032] Figure 8 The DSC curve (heating rate 10°C / min) of Camp1 (Exp. ID SSm14) is shown. The DSC shows a broad endothermic reaction at temperatures between 25 and 100°C due to the loss of water, and another endothermic reaction at 164°C, possibly related to the melting of the anhydrous form.

[0033] Fig. 9 The liquid chromatography-mass spectrometry analysis of Camp1 (Exp. ID SSm14) is shown. The purity of the active ingredient is 100%.

[0034] Fig.10Overlay of H-NMR spectra (500 MHz, DMSO-d6) of ABN401 free base (green) and Camp1 (Exp. ID SSm14) (red) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and signals at 2.0-0.8 ppm are fluorescently labeled.

[0035] Fig.11 Shown are high temperature X-ray crystallography (HT-XRPD) patterns of Camp1 (Exp. ID SSm14) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) for 2 days.

[0036] FIG12 shows TGA (A) and TGMS (B) analysis (heating rate 10° C. / min) of Camp2 (Exp. ID SSm60, solid phase after evaporation of ML). A mass loss of 1.6% due to water is shown at temperatures between 25 and 80° C. Thermal decomposition is shown at temperatures above about 240° C. The heat flow signal analyzed by TGA shows a significant endothermic reaction at a temperature of about 200° C., which may be related to the melting of the anhydrous form.

[0037] Fig.13 The DSC curve (heating rate 10°C / min) of Camp2 (Exp. ID SSm60) is shown. The DSC exhibits a broad endothermic reaction at 25-70°C due to water loss, and another endothermic reaction at 208.9°C, which may be related to the melting of the anhydrous form.

[0038] 14 shows TGA (A) and TGMS (B) analysis of Camp2 (Exp. ID SSm60) after further drying under reduced pressure at 80°C for 1 hour (heating rate 10°C / min). A mass loss of 1.6% due to water was observed at 25-70°C.

[0039] Fig.15 The liquid chromatography mass spectrometry analysis of Camp2 (Exp. ID SSm60) is shown. The purity of the active ingredient is 100%.

[0040] Fig.16 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of ABN401 free base (green) and Camp2 (Exp. ID SSm60) (red) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and signals at 2.0 to 0.8 ppm are fluorescently labeled.

[0041] Fig.17HR-XRPD (lower) and HT-XRPD (upper) of Camp2 (Exp. ID SSm73) are shown.

[0042] FIG18 shows TGA (A) and TGMS (B) analysis of Camp2 (Exp. ID SSm73) (heating rate 10°C / min). A mass loss of 1.6% due to water was shown at temperatures between 25 and 80°C. Thermal decomposition was shown at temperatures above about 240°C. The heat flow signal analyzed by TGA showed an obvious endothermic reaction at a temperature of about 200°C, which may be related to the melting of the anhydrous form.

[0043] Fig.19 The DSC curve of Camp2 (Exp. ID SSm73) (heating rate 10°C / min) is shown. The DSC shows a broad endothermic reaction at 25-80°C due to water loss and another significant endothermic reaction at 208.6°C, which may be related to the melting of the anhydrous form.

[0044] Fig. 20 The liquid chromatography mass spectrometry analysis of Camp2 (Exp. ID SSm73) is shown. The purity of the active ingredient is 99.7%.

[0045] Fig.21 ABN401 free base (blue), Camp2 (Exp. ID SSm60) (green) and Camp2 (Exp.ID Overlay of the H-NMR spectra (500 MHz, DMSO-d6) of SSm73 (red). The peaks of CI are fluorescently labeled at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and signals at 2.0 to 0.8 ppm.

[0046] FIG. 22 shows the results of DVS measurement of Camp2 (Exp. ID SSm73), showing the change in mass (A) and the change in the isotherm curve (B).

[0047] Fig.23 HR-XRPD patterns of camphorsulfonate (Exp. ID SSm73) before (Camp2, bottom) and after (Camp4, top) DVS analysis are shown.

[0048] Figure 24 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN78) exposed to 25°C / 60% RH for 1 month and (B) Form A (Exp. ID GEN74) exposed to 40°C / 75% RH for 1 month. Before thermal decomposition at a temperature of about 230°C, 3.7% and 4.0% mass loss were respectively exhibited due to water.

[0049] Figure 25 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN79) exposed to 25°C / 60% RH for 3 months and (B) Form A (Exp. ID GEN75) exposed to 40°C / 75% RH for 3 months. Before thermal decomposition, 4.1% and 4.4% mass losses were observed respectively due to water.

[0050] Figure 26 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN80) exposed to 25°C / 60% RH for 15 months and (B) Form A (Exp. ID GEN77) exposed to 40°C / 75% RH for 15 months. Before thermal decomposition at a temperature of about 230°C, 3.3% and 3.7% mass loss were respectively exhibited due to water.

[0051] Figure 27 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN81) exposed to 25°C / 60% RH for 24 months and (B) Form A (Exp. ID GEN76) exposed to 40°C / 75% RH for 24 months. Before thermal decomposition, 5.3% and 5.2% mass loss were observed respectively due to water.

[0052] Fig.28 Shown is the LC-MS analysis of Form A (Exp. ID GEN81) exposed to 25°C / 60%RH for 24 months. The purity of the active ingredient is 87.2%.

[0053] Fig.29 Shown is the LC-MS analysis of Form A (Exp. ID GEN76) exposed to 40°C / 75%RH for 24 months. The purity of the active ingredient is 90.7%.

[0054] Fig.30Overlapping high-efficiency X-ray crystallography patterns of Camp2 (Exp. ID SSm73) are shown in scale, showing, from bottom to top, Camp2 (Exp. ID GEN50) exposed to 25°C / 60% RH for 1 month, Camp2 (Exp. ID GEN54) exposed to 40°C / 75% RH for 1 month, Camp2 (Exp. ID GEN51) exposed to 25°C / 60% RH for 3 months, Camp4 (Exp. ID GEN55) exposed to 40°C / 75% RH for 3 months, Camp2 (Exp. ID GEN52) exposed to 25°C / 60% RH for 15 months, Camp4 (Exp. ID GEN56) exposed to 40°C / 75% RH for 15 months, Camp2 (Exp. ID GEN53) exposed to 25°C / 60% RH for 24 months, Camp3+E (Exp. ID GEN57) after exposure to 40°C / 75%RH for 24 months.

[0055] FIG. 31 shows (A) Camp 2 (Exp. ID GEN50) and (B) Exposure to 40 TGMS analysis of Camp2 (Exp.ID GEN54) at 1 month at ℃ / 75%RH (add The results were as follows: before thermal decomposition at about 240°C, the mass losses due to water were 1.6% and 1.8%, respectively.

[0056] FIG32 shows the results of TGMS analysis (heating rate of 10° C. / min) of (A) Camp2 (Exp. ID GEN51) exposed to 25° C. / 60% RH for 3 months and (B) Camp2 (Exp. ID GEN55) exposed to 40° C. / 75% RH for 3 months. Before thermal decomposition at about 240° C., 4.1% and 4.4% mass losses were respectively shown due to water. The heat flow signal showed an endothermic reaction at a temperature of about 200° C. (GEN51) or 150° C. (GEN55), respectively, and then a widespread endothermic reaction occurred due to the dissolution of water.

[0057] FIG33 shows the results of TGMS analysis (heating rate of 10° C. / min) of (A) Camp2 (Exp. ID GEN52) exposed to 25° C. / 60% RH for 15 months and (B) Camp2 (Exp. ID GEN56) exposed to 40° C. / 75% RH for 15 months. Before thermal decomposition at about 230° C., 1.6% and 6.9% mass loss were respectively shown due to water. The heat flow signal showed an endothermic reaction at a temperature of about 200° C. (GEN52) or 150° C. (GEN56), respectively, and then a widespread endothermic reaction occurred due to the dissolution of water.

[0058] FIG34 shows the results of TGMS analysis (heating rate of 10° C. / min) of (A) Camp2 (Exp. ID GEN53) exposed to 25° C. / 60% RH for 24 months and (B) Camp2 (Exp. ID GEN57) exposed to 40° C. / 75% RH for 24 months. Before thermal decomposition, 1.9% and 6.7% mass losses were respectively shown due to water. The heat flow signal showed an endothermic reaction at a temperature of about 150° C. (GEN56), and then a widespread endothermic reaction occurred due to the dissolution of water.

[0059] Fig.35 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN50) exposed to 25°C / 60% RH for 1 month. The purity of the active ingredient is 99.8%.

[0060] Fig.36 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN54) exposed to 40°C / 75%RH for 1 month. The purity of the active ingredient is 99.8%.

[0061] Fig.37 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN51) exposed to 25°C / 60%RH for 3 months. The purity of the active ingredient is 99.7%.

[0062] Fig.38 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN55) exposed to 40°C / 75%RH for 3 months. The purity of the active ingredient is 99.3%.

[0063] Fig.39 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN52) exposed to 25°C / 60%RH for 15 months. The purity of the active ingredient is 97.3%.

[0064] Fig.40 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN56) exposed to 40°C / 75%RH for 15 months. The purity of the active ingredient is 93.7%.

[0065] Fig.41 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN53) exposed to 25°C / 60%RH for 15 months. The purity of the active ingredient is 100%.

[0066] Fig.42Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN57) exposed to 40°C / 75%RH for 15 months. The purity of the active ingredient is 88.6%.

[0067] Fig.43 Shown are high temperature X-ray crystallography (HT-XRPD) patterns of Camp1 (Exp. ID SSm14) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) after thermocycling with MTBE (Exp. ID GEN21) for 2 days in a salt screen.

[0068] FIG44 shows TGA (A) and TGMS (B) analysis of Camp1 (Exp. ID SSm14) obtained from MTBE (Exp. ID GEN21) thermocycling (heating rate 10°C / min). According to the MS signal, 4.1% of mass loss was caused by water and MTBE at temperatures between 25 and 200°C. Thermal decomposition of the salt was shown at a temperature of about 240°C, and a broad endothermic reaction due to melting of the anhydride of the salt was shown at a temperature of about 155°C according to the heat flow signal of the TGA analysis.

[0069] Figure 45 shows TGA (A) and TGMS (B) analysis of Camp1 obtained from thermal cycling with water (Exp. ID GEN23) (heating rate 10°C / min). According to the MS signal, 3.81% mass loss due to water was shown at temperatures between 25 and 200°C. Thermal decomposition of the salt was shown at a temperature of about 240°C.

[0070] Fig.46 The DSC curve of Camp 1 obtained from the thermal cycle of MTBE (Exp. ID GEN21) is shown (heating rate is 10°C / min). The DSC analysis results show that there is a wide range of endothermic reactions at temperatures of 25-120°C due to the loss of water and MTBE. In addition, a subsequent endothermic reaction is exhibited at a temperature of 158.8°C, which is believed to be caused by the melting of the potential anhydrous salt.

[0071] Fig.47 The DSC curve of Camp1 obtained from the thermal cycle of water (Exp. ID GEN23) is shown (heating rate is 10°C / min). The DSC analysis results show that a broad endothermic reaction is caused by the loss of water at a temperature of 25-80°C. In addition, a broad endothermic reaction is exhibited at a temperature of 130-180°C, which is believed to be caused by the melting of the potential anhydrous salt.

[0072] Fig.48The liquid chromatography-mass spectrometry analysis of Camp1 (Exp. ID GEN21) is shown. The purity of the active ingredient is 98.6%.

[0073] Fig.49 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of Camp1 (Exp. ID GEN21, red) and Camp1 (Exp. ID SSm14, green) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and signals at 2.0 to 0.8 ppm are fluorescently labeled.

[0074] Fig.50 Shown are high temperature X-ray crystallography (HT-XRPD) patterns of Camp2 (Exp. ID SSm60) before (lower) and after (upper) exposure to AAC (40°C / 75% RH) for 2 days after thermal cycling in ethanol (Exp. ID GEN17).

[0075] FIG51 shows TGA (A) and TGMS (B) analysis of Camp2 obtained after thermal cycling (Exp. ID GEN17) in ethanol (heating rate of 10°C / min). A mass loss of 1.7% was caused by water at temperatures between 25 and 180°C. Thermal decomposition was shown at temperatures above about 240°C. The heat flow signal analyzed by TGA showed a clear endothermic reaction at a temperature of about 200°C, which may be related to the melting of the anhydrous form.

[0076] Fig.52 The DSC curve of Camp2 obtained from the thermal cycle of (Exp. ID GEN17) in ethanol (heating rate is 10°C / min) is shown. The DSC analysis results show that there is a broad endothermic reaction due to the loss of water at a temperature of 25-60°C. In addition, an endothermic reaction occurs at a temperature of 207.4°C, which is believed to be caused by the melting of the potential anhydrous salt.

[0077] Fig.53 LC-MS analysis of Camp2 obtained from thermal cycling in ethanol (Exp. ID GEN17) is shown. The purity of the active ingredient is 97.9%.

[0078] Fig.54 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of Camp2 (Exp. ID GEN17, red) and Camp2 (Exp. ID SSm73, green) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and signals at 2.0 to 0.8 ppm are fluorescently labeled.

[0079] Fig.55 HT-XRPD results of Camp4 obtained after DVS analysis of Camp2 (Exp. ID SSm70 after DVS) after thermal cycling in n-heptane (Exp. ID GEN19), high efficiency X-ray crystallography (HT-XRPD) patterns before (bottom) and after (top) exposure to AAC (40°C / 75%RH) for 2 days.

[0080] Figure 56 shows TGA (A) and TGMS (B) analysis of Camp4 obtained after thermal cycling in n-heptane (Exp. ID GEN19) (heating rate 10°C / min). A mass loss of 3.8% due to water and heptane was shown at temperatures between 25 and 200°C. Thermal decomposition was shown at temperatures above about 240°C.

[0081] Figure 57 shows TGA (A) and TGMS (B) analysis of Camp4 obtained after thermal cycling (Exp. ID GEN26) in THF / water (95 / 5) (heating rate 10°C / min). A mass loss of 9.1% due to water and THF was shown at temperatures between 25 and 230°C. Thermal decomposition was shown at temperatures above about 240°C.

[0082] Fig.58 The DSC curve of Camp4 obtained after thermal cycling in n-heptane (Exp. ID GEN19) is shown (heating rate is 10°C / min). The DSC analysis results show that a wide range of endothermic reactions are caused by the loss of water at temperatures between 25 and 100°C. In addition, an endothermic reaction occurs at a temperature of 150.4°C, which is believed to be caused by the loss of heptane.

[0083] Fig.59 The DSC curve of Camp4 obtained after thermal cycling (Exp. ID GEN26) in THF / water (95 / 5) (heating rate of 10°C / min) is shown. The DSC analysis results show that a wide range of endothermic reactions are caused by the loss of water at temperatures between 25 and 140°C. In addition, a significant endothermic reaction occurs between 160 and 225°C, which is believed to be caused by the loss of THF.

[0084] Fig.60 The liquid chromatography mass spectrometry analysis of Camp4 obtained after thermal cycling in n-heptane (Exp. ID GEN19) is shown. The purity of the active ingredient is 99.5%.

[0085] Fig.61 The liquid chromatography mass spectrometry analysis of Camp4 obtained after thermal cycling (Exp. ID GEN26) in THF / water (95 / 5) is shown. The purity of the active ingredient is 95.4%.

[0086] Fig.62 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of Camp4 (Exp. ID GEN19, red) and Camp2 (Exp. ID SSm73, green) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and signals at 2.0 to 0.8 ppm are fluorescently labeled.

[0087] Fig.63 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of Camp4 (Exp. ID GEN26, red) and Camp2 (Exp. ID SSm73, green) is shown. Peaks corresponding to CI are fluorescently labeled at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and signals at 2.0 to 0.8 ppm. Additional chemical shifts were confirmed at 9.66, 5.90, 4.29, 3.86-3.64, 2.44 and 1.6-1.8 ppm. DETAILED DESCRIPTION

[0088] The novel salt of the compound effectively inhibits the activity of c-Met tyrosine kinase, and thus can be usefully used as a therapeutic agent for various hyperproliferative diseases associated with excessive cell proliferation and growth due to abnormal kinase activity, such as cancer, psoriasis, rheumatoid arthritis, diabetic retinopathy, etc. Also provided is a pharmaceutical composition for inhibiting c-Met tyrosine kinase activity and a pharmaceutical composition for preventing or treating a hyperproliferative disorder, comprising the novel salt compound as an active ingredient.

[0089] In one aspect, the camphorsulfonate is the S-enantiomer of the triazolopyrazine derivative represented by the chemical formula 1. Preferably, the triazolopyrazine derivative represented by the chemical formula 1 is an optically pure substance. In another aspect, the optical purity is at least 95%, at least 97%, at least 99% or substantially 100%.

[0090] In one aspect, the camphorsulfonate is formed in one of the forms of Camp1, Camp2, Camp4, Camp5 or Camp6. The camphorsulfonate is likely to be in the form of Camp2. In one aspect, the camphorsulfonate has a physical stability of at least 2 days at a temperature of 20-50° C. and a relative humidity of 35%-80%. In one aspect, the camphorsulfonate has a physical stability of 24 months under ambient conditions. Furthermore, the purity of the active ingredient of the camphorsulfonate is at least 95%, and the purity is preferably about 97.9%.

[0091] In one aspect, the high performance X-ray powder diffraction (HT-XRPD) spectrum of the camphorsulfonate salt consists of characteristic peaks at 2θ of 14-14.5° and 2θ of 16-170° (deg). Preferably, the HT-XRPD spectrum of the camphorsulfonate salt actually has the following characteristic peaks.

[0092] Table 1

[0093]

[0094] or

[0095] Table 2

[0096]

[0097]

[0098] In one aspect, the present invention provides a method for preparing the camphorsulfonate, comprising: step a), adding the compound of Chemical Formula 1 to a reactor containing a solvent; step b), stirring the solvent and the compound in the reactor; step c), adding 10-camphorsulfonic acid to the solution prepared in step b); and step d), cooling the solution prepared in step c) to precipitate the camphorsulfonate.

[0099] In one aspect, the solvent may be selected from acetonitrile, acetone, 1-2-dimethoxyethane, n-heptane, isopropanol, water or tetrahydrofuran (THF). In one aspect, the 10-camphorsulfonic acid added to the solution prepared in step b) is added in an equivalent of 1:0.5 to 1:1.5 relative to the compound of chemical formula 1. Preferably, the equivalent ratio is 1:1.0 to 1:1.2, and the solvent is acetonitrile. In one aspect, the step b) is performed at a temperature of about 45°C to 55°C for at least 1 hour.

[0100] In one aspect, the present invention provides a pharmaceutical composition comprising the camphorsulfonate and a pharmaceutical carrier. The pharmaceutically acceptable carrier contained in the pharmaceutical composition is one or more components selected from the group consisting of lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginate, gelatin, calcium silicate, microcrystalline cellulose, polyvinyl pyrrolidone, cellulose, water, syrup, methylcellulose, methyl hydroxybenzoate, propyl hydroxybenzoate, talc, magnesium stearate and mineral oil. In addition to the above ingredients, the pharmaceutical composition provided by the present invention may also include lubricants, wetting agents, sweeteners, flavoring agents, emulsifiers, suspending agents, preservatives, etc.

[0101] In one aspect, the present invention provides a method for reducing the activity of c-Met kinase by administering a pharmaceutical composition containing an effective amount of the camphorsulfonate to a patient in need thereof. In one aspect, the patient is a patient suffering from a disease associated with excessive cell proliferation and activation, for example, the disease may be lung cancer, colorectal cancer, pancreatic cancer, rectal cancer, ovarian cancer, kidney cancer, prostate cancer or brain tumor. In one aspect, the method is a method for treating or preventing excessive cell proliferation and activation.

[0102] <General>

[0103] Table 3

[0104]

[0105] <Solvent>

[0106] Table 4

[0107]

[0108] <Counter ions>

[0109] Table 5

[0110] HCl Hydrochloride acid Mes Methanesulfonic acid Bes Benzenesulfonic acid Mae Maleic acid Esy Ethanesulfonic acid Camp D(+)-10-Camphorsulfonic acid Mao Malonic acid Fum Fumaric acid Cit Citric acid Mal (-)-L-Malic acid Suc Succinic acid Gal Gallic acid

[0111] The present invention will be described in detail by the following examples, but the technical scope of the present invention is not limited to the examples.

[0112] Example

[0113] The compound of Chemical Formula 1 (ABN-401) was provided by ABION, and the other compounds were provided by Fisher Scientific, Sigma Aldrich or VWR. The compounds used were of researcher grade, and the solvents used for LCMS analysis were of LCMS grade.

[0114] Determine solubility

[0115] Solubility was determined by adding small aliquots of solvent (50 μL up to 1 mL, 100 μL above 1 mL) to the starting material until complete dissolution occurred or a maximum volume of 4 ml was reached.

[0116] Then, the solid obtained after evaporating the solvent was analyzed by HT-XRPD, and the experimental results and details thereof are shown in Table 1.

[0117] (Form 1)

[0118] Table 6

[0119]

[0120]

[0121] Thermal stability

[0122] Thermal stability experiments of ABN-401 were performed to confirm the chemical stability of the dissolved starting material when exposed to elevated temperatures.

[0123] A solution of ABN-401 with a concentration of about 0.3 mg / mL was prepared in a solvent consisting of acetone, 1,2-dimethoxyethane, and acetonitrile. The solution was exposed to room temperature for 1 hour, and then two sample aliquots were sequentially exposed to temperatures of 50°C and 80°C for 1 hour, respectively. The solution was analyzed by LCMS.

[0124] Furthermore, the sample placed at room temperature for 24 hours was measured again to examine the chemical deterioration of the compound over time.

[0125] No serious chemical deterioration of the samples was observed at the temperatures of 50° C. and 80° C. The results are shown in Table 2.

[0126] (Table 2) LCMS analysis results in thermal stability experiment

[0127] Table 7

[0128]

[0129]

[0130] Salt screening experiment

[0131] The ABN-401 solutions in acetone, 1,2-dimethoxyethane and acetonitrile were prepared at concentrations of about 25, 13 and 8 mg / ml, respectively, and the salt screening experiment was initiated.

[0132] Counterions were added to the API solution at a ratio of 1:1.1, 1:2.1, and 1:3.1. The experiment resulted in a temperature profile that included three heating-cooling cycles between 5°C and 50°C, and aging at 25°C for 3 days ( Figure 1 ).

[0133] After the aging time was over, the solid particles were separated from the liquid phase and dried under reduced pressure at 50° C. and then analyzed by HT-XRPD.

[0134] The solution and mother liquor phase were evaporated at room temperature and the remaining solid particles were analyzed by HT-XRPD. All solid particles were then exposed to accelerated aging conditions of 40°C / 75%RH for 48 hours and re-measured by HT-XRPD to test their physical stability.

[0135] Scaling up salt

[0136] The camphorsulfonate salt Camp2 was scaled up to 0.5 gram (Exp. ID SSm71). 300 mg of the free base form was dissolved in 15 ml of ACN at 20 mg / ml at 50°C.

[0137] Camphor-10-sulfonic acid (136 mg) was added to give a molar ratio of API:CI of 1:1.1. The suspension was heated to 50°C and stirred at 50°C for 1 hour. The salt suspension was cooled to 25°C and aged for 72 hours. Precipitation of the salt occurred during cooling. The solid particles were isolated and dried under reduced pressure at 50°C and 10 mbar, and then analyzed by HT- / HR-XRPD, TGA / TGMS, DSC, LCMS, 1H-NMR and DVS.

[0138] Camphorsulfonate Mes2 was scaled up to 0.5 gram scale (Exp. ID SSm71). 500 mg of the free base form was dissolved in 23 ml of acetone to a concentration of 26 mg / ml. Methanesulfonic acid (1 M in water) was added to give a molar ratio of API:CI of 1:2.1. Precipitation of the salt was observed after addition of the counterion. The suspension was heated to 50°C and stirred continuously at 50°C for 8 hours. The salt suspension was cooled to 25°C. The solid particles were isolated and dried under reduced pressure at 50°C, 10 mbar, and then analyzed by HT- / HR-XRPD, TGA / TGMS, DSC, LCMS, 1H-NMR and DVS.

[0139] The maleate salt Mae2 was scaled up to 0.3 gram level (Exp.ID SSm75). 300 mg of the free base form was dissolved in 5 ml of acetone at a temperature of 50°C to a concentration of 60 mg / ml. Maleic acid suspension (130 mg) was added to the free base form to give a molar ratio of API:CI of 1:2.1. The suspension was heated to 50°C and stirred continuously for 1 hour at a temperature of 50°C. The salt suspension was cooled to 25°C and aged for 72 hours. Due to the high viscosity of the salt suspension, 2 ml of acetone was added and shaken to remove unreacted API or maleic acid. The solid particles were separated and dried under reduced pressure at 50°C and 10 mbar, and then analyzed by HT- / HR-XRPD, TGA / TGMS, DSC, LCMS, 1H-NMR and DVS.

[0140] Physical and chemical stability

[0141] The camphorsulfonate (Mes2), camphorsulfonate (Camp2) and maleate (Mae2) were subjected to physical stability experiments at specific temperature and relative humidity (25° RH and 40° RH) for 2 years.

[0142] The above stability test was also performed on the free base form of ABN-401 as a reference material.

[0143] The vials containing the particles were subjected to XRPD, TGMS and HPLC tests at 1, 3, 15 and 24 months to confirm whether there were any particular changes in the solid particles and the water and solvent contents, and to confirm whether the storage state of the compound was deteriorated when stored under different conditions.

[0144] Table 3: Conditions used for stability testing of the camphorsulfonate salt (Camp2), maleate salt (Mae2), camphorsulfonate salt (Mes2) and the free base form (FB) of ABN-401

[0145] Table 8

[0146]

[0147]

[0148] Screening of crystal forms of maleate and camphorsulfonate

[0149] The maleate and camphorsulfonate salts were evaluated for changes in crystalline form by thermal cycling of 15 solvents. The salts were prepared by freeze drying to yield amorphous salts, for which several attempts were made and the experimental conditions are shown in Table 4.

[0150] (Table 4): Experimental conditions for freeze drying to produce amorphous salts. The symbol lc indicates that very small crystals were produced.

[0151] Table 9

[0152]

[0153]

[0154]

[0155] Based on the results, the most appropriate conditions were reproduced on a large scale in order to generate material for screening crystal forms. The scale-up conditions are as follows.

[0156] A solution of ABN-401 (735 mg) was prepared at a concentration of 147 mg / ml (Exp. ID GEN10) in a 1,4-dioxane / water (50 / 50) solvent containing 1 molar equivalent of camphor-10-sulfonic acid. The solution was divided into 16 vials.

[0157] A solution of ABN-401 (722 mg) was prepared at a concentration of 60 mg / ml (Exp. ID GEN11) in a tetrahydrofuran (THF) / water (50 / 50) solvent containing 2 molar equivalents of maleic acid. The solution was divided into 16 vials.

[0158] The solution was frozen in liquid nitrogen and placed under vacuum using a freeze dryer. A sample of the freeze dried solid was analyzed by HT-XRPD and TGMA to confirm the content of the solvent, and H-NMR to confirm the form of the salt.

[0159] To the vial containing the crystals was added an aliquot of solvent until a thin suspension was obtained.

[0160] To obtain the temperature profile of the vial, the vial was thermally cycled 3 times between 50 and 5°C and aged at room temperature for 2 days. The results are shown in Figure 2 middle.

[0161] After the temperature profile, the solid and liquid phases were separated. The solid phase was dried overnight under vacuum at 50°C, 10 mbar and then analyzed. An aliquot of the liquid from the mother phase of each experiment was filtered and analyzed by HPLC. Two stock solutions were prepared by determining the concentration of the API in the solution by a calibration line.

[0162] The liquid solvent was evaporated in the atmosphere and the resulting solids were analyzed by XRPD. All solids were gradually exposed to accelerated ripening conditions (AAC. 40°C / 75%RH) for 2 days and re-analyzed by HT-XRPD.

[0163] High-efficiency X-ray powder diffraction analysis

[0164] HT-XRPD patterns were collected by a Crystal T2 high performance XRPD apparatus.

[0165] The plate was mounted on a Bruker General Area Detector Diffraction System (GADDS) equipped with a VANTEC-500 gas area detector for correction of intensity and shape. The accuracy calibration of the peak positions was performed according to the NIST SRM1976 standard (Corundum).

[0166] Data collection was performed at room temperature using a Cu Ka monochromator with a 2θ range of 1.5° to 41.5°, which is the most unique method for XRPD patterns. The diffraction patterns of each well were collected by exposing each frame for 90 seconds in two 2θ ranges (1.5°≤2θ≤21.5° first frame, 19.5°≤2θ≤41.5° second frame).

[0167] The XRPD pattern is subjected to any operation to remove background or smooth the curve.

[0168] The support material used during HT-XRPD measurements is transparent to X-rays and contributes only very slightly to the background.

[0169] High-resolution X-ray powder diffraction analysis

[0170] Powder data were collected by D8 diffraction analysis, here using Cu K1 monochromated germanium at room temperature.

[0171]

[0172] The data were collected using a LynxEye detector for solids at 22 sec / step over a 2θ range of 4° to 45° and a 2θ step size of 0.016°. The sample was measured using a glass capillary with an outer diameter of 0.3 mm and a length of 8 mm.

[0173] TGMS analysis

[0174] The mass loss due to the loss of water and solvent in the crystals was determined by TGA. The weight of the sample was monitored and heated with a TGA / DSC3+STARe system to obtain a weight-temperature curve and a heat flow signal as the result. The TGA / DSC3+ results were temperature corrected using indium and aluminum samples. The sample was loaded into a 100 μL aluminum crucible and sealed. A filling hole was formed in the seal, and the crucible was heated from 25°C to 300°C at a heating rate of 10° during the TGA process. Dry nitrogen was used during the purge.

[0175] The gases emitted from the TGA samples were analyzed by an Omnistar GSD 301T2 (Pfeiffer Vacuum GmbH, Germany) mass spectrometer. The analyzer can perform mass analysis at temperatures in the range of 0-200 amu.

[0176] DSC analysis

[0177] DSC thermograms were recorded by a heat flux DSC3+STARe system. The DSC3+ was calibrated for temperature and enthalpy using trace amounts of indium (mp=156.6°; δHf=28.45 J / g) and zinc (mp=419.6°; δHf=107.5 J / g).

[0178] The sample was sealed in a standard 40 μL aluminum pan and filled with a well, and heated during DSC from 25° C. to 300° C. at a heating rate of 10°. Dry nitrogen was used during the purge at a flow rate of 50 mL / min.

[0179] H-NMR analysis

[0180] H-NMR spectra were recorded at room temperature using a 500 MHz Bunker instrument. The samples were dissolved in DMSO and analyzed. The data were processed using the ACD Labs software Spectrus processor.

[0181] LCMA analysis

[0182] Characterization of the starting material and purification of the new crystalline form from the free base form

[0183] Method name: S19061_0.3M

[0184] Sample: 0.3 mg / ml concentration, diluent: acetonitrile

[0185] (Form 5)

[0186] Table 10

[0187]

[0188]

[0189] Analysis and purification of new crystalline salt

[0190] Method name: S19061_01.M

[0191] Sample: 0.3 mg / ml concentration, diluent: acetonitrile / water (50 / 50) (Table 6)

[0192] Table 11

[0193]

[0194]

[0195] DVS Analysis

[0196] The difference in hygroscopicity of different forms of solid substances is a measure of the relative stability of each substance when the relative humidity increases. The isothermal hygroscopicity of trace samples is obtained by the DVS-1 system. The device is suitable for measuring very trace samples with an accuracy of 0.1 μg. At a constant temperature of 25°C, the relative humidity (40-95-40% RH) is changed in the process of hygroscopicity-dehumidification-hygroscopicity, usually each step (10% relative humidity step) is maintained for 60 minutes. At the end of the DVS experiment, the sample is measured by XRPD.

[0197] Hygroscopicity is classified according to the European Pharmaceutical Hygroscopicity Classification.

[0198] At 25°C / 80%RH (24 hours), the moisture absorption rate was graded as follows.

[0199] Mass change <0.2% - non-hygroscopic

[0200] Mass change > 0.2% and < 2% - slightly hygroscopic

[0201] Mass change >2% and <15% - Slightly hygroscopic

[0202] Mass change > 15% - Very hygroscopic

[0203] Camphorsulfonate

[0204] Figure 5 XRPD patterns of all camsylate salts are shown in the free base form (Form A).

[0205] Camp1 is a camphorsulfonate obtained by adding camphor-10-sulfonic acid to acetone and 1,2-dimethoxyethane crystallization solvents to obtain a molar ratio of API:CI of 1:1.

[0206] Table 7 shows the experimental conditions used to obtain Camp1. The solid selected for the subsequent characterization process is the crystalline salt formed when camphor-10-sulfonic acid is added in acetone at 1 molar equivalent (Exp. ID SSm14). Camp1 showed physical stability after exposure to AAC (40° RH) for 2 days ( Figure 6 ).

[0207] (Table 7) Experimental conditions used to obtain Camp1

[0208] Table 12

[0209]

[0210] TGA / TGMS analysis of Camp1 showed a mass loss of 3.3% between 25 and 120°C due to water (3.3% is equivalent to 1.5 water molecules per salt molecule). Thermal decomposition was observed at temperatures above 240°C. The heat flow signal showed a clear endothermic reaction around 160°C, which was probably caused by the melting of the anhydride of the salt.

[0211] The heat flow signal of TGA exhibits a broad endothermic reaction around 160 °C due to mass loss, which is associated with the melting of the anhydrous form.

[0212] DSC analysis of Camp1 showed a broad endothermic reaction from 25°C to 120°C, which may be related to the loss of water. A double endothermic reaction occurred around 164°C, which may be caused by the melting of the underlying anhydrous salt.

[0213] The chemical purity of the Camp1 analyzed by LCMS showed 100%, which means that the API was present in the solid phase of Camp1.

[0214] The 1H-NMR analysis results of Camp1 are shown in Fig.10 The shift of API resonances seen in the spectrum of Camp 1 indicated a proton transfer from the acidic counterion to the free base. The API:CI ratio was shown to be 1:1, with residual acetone observed at 2.2 ppm.

[0215] Camp2 is a camphorsulfonate salt (Exp. ID SSm60) obtained in a crystallization experiment by adding camphor-10-sulfonic acid to ACN solvent to make the molar ratio of API:CI 1:1. Table 8 shows the experimental conditions used to obtain Camp2. Camp2 showed physical stability after exposure to AAC (40° RH) for 2 days.

[0216] (Table 8): Experimental conditions used to obtain Camp2

[0217] Table 13

[0218]

[0219] TGA / TGMS analysis of Camp 2 showed a mass loss of 1.6% due to water between 25 and 150°C based on the MS signal (1.6% corresponds to 0.7 water molecules per salt molecule). Thermal decomposition was observed at temperatures above 240°C.

[0220] The heat flow signal of the TGA showed an extensive endothermic reaction at a temperature of about 200°C due to the melting of the anhydride of the salt, followed by decomposition.

[0221] The DSC analysis results of Camp 2 showed a broad endothermic reaction from 25°C to 70°C, which may be related to the loss of water. An endothermic reaction occurred around 208.9°C, which may be caused by the melting of the underlying anhydrous salt.

[0222] The Camp2 sample (Exp. ID SSm60) was dried under vacuum at 80°C to prevent melting of the potential anhydrous salt at 208.9°C as shown in DSC. The resulting solid was analyzed by HT-XRPD and TGMS. The residual Camp2 solid contained 1.9% water.

[0223] The chemical purity of the Camp2 determined by LCMS was 100%, which confirmed the presence of the API in the solid phase.

[0224] The 1H-NMR analysis results of Camp2 are shown in Fig.16 The shift of API resonances that appears in the spectrum of Camp2 indicates a proton transfer from the acidic counterion to the free base, indicating that the API:CI ratio is 1:1.

[0225] Characterization and analysis results of Camp2

[0226] HT-XRPD analysis results confirmed the crystallization of Camp2 (Exp.ID SSm73) in the scale-up experiment ( Fig.17 ). The high-resolution XRPD (HR-XRPD) pattern of Camp2 was not indexed.

[0227] TGA / TGMS analysis of dried Camp2 showed a mass loss of 1.6% between 25 and 80°C (Figure 18), which was presumably due to water loss based on the MS signal (1.6% is equivalent to 0.7 water molecules per salt molecule). Thermal decomposition of Camp2 was observed at temperatures above 240°C.

[0228] DSC analysis results of Camp2 showed that there was a broad endothermic reaction associated with water loss between 25 and 80 °C ( Fig.19 ). A second obvious endothermic reaction was observed at a temperature of 208.6°C, which may be related to the melting process of the anhydrous salt. The chemical purity of Camp2 determined by LCMS was 99.7%, which confirmed the presence of API in the solid phase of Camp2.

[0229] The H-NMR analysis results of Camp2 are shown in Fig.21 The shift in the API resonance observed in the Camp2 spectrum indicates a proton transfer from the acidic counterion to the free base. The API:CI ratio is 1:1.

[0230] Figure 22 shows the results of the DVS measurement of Camp2. The first moisture absorption of the half cycle showed that the water absorption rate reached 15.6% at a relative humidity of 95% (a mass change of 14.1% occurred when the relative humidity changed from 40% to 95%). The curve representing the mass change shows that the absorption of water did not reach equilibrium at a relative humidity of 90-95%. In the dehumidification cycle from 95% to 0% relative humidity, water was discharged. The mass change in the second half of the absorption cycle (from 0% to 40% relative humidity) was 6.6%. The absorption of water is irreversible, which indicates a change in form. The new form of Camp4 was confirmed by HT-XRPD in the solid phase. ( Fig.23 )

[0231] The DVS analysis results showed that the mass change at 80% relative humidity was about 1.4%, which indicates that the substance is slightly hygroscopic according to the European Classification of Hygroscopicity of Pharmaceuticals.

[0232] Stability of the free base form

[0233] Form A was exposed to 25°C / 60% RH and 40°C / 75% RH for 3 months for TGA analysis, and the results are shown in Fig.25a , Fig.25b The samples exposed to 25°C / 60%RH and 40°C / 75%RH for 3 months showed a mass loss of 4.1% and 4.4%, respectively. The heat flow analysis results showed that an extensive endothermic reaction due to water loss occurred at a temperature of 140°C corresponding to the melting of Form A. Thermal decomposition of both samples was observed at a temperature of 230°C.

[0234] Form A was exposed to 25°C / 60% RH and 40°C / 75% RH for 15 months and TGA analysis was performed and the results are shown in Fig.26a , Figure 26bThe samples exposed to 25°C / 60%RH and 40°C / 75%RH for 15 months showed a mass loss of 3.3% and 3.7%, respectively. The heat flow analysis results showed that an extensive endothermic reaction due to water loss occurred at a temperature of 140°C corresponding to the melting of Form A. Thermal decomposition of both samples was observed at a temperature of 230°C.

[0235] Form A was exposed to 25°C / 60% RH and 40°C / 75% RH for 24 months and TGA analysis was performed and the results are shown in Fig.27a , Figure 27b The samples exposed to 25°C / 60%RH and 40°C / 75%RH for 42 months showed a mass loss of 5.3% and 5.2%, respectively. The heat flow analysis results showed that an extensive endothermic reaction due to water loss occurred at a temperature of 140°C corresponding to the melting of Form A. No thermal decomposition occurred at temperatures below 200°C.

[0236] The Form A was exposed to 25°C / 60%RH (Exp. ID GEN81) and 40°C / 75%RH (Exp. ID GEN76) for 24 months, and the chemical purity determined by LCMS was 87.2% and 90.7%, respectively ( Fig.43 , Figure 44). This confirms that the compound changes under both conditions.

[0237] Stability of Camphorsulfonate

[0238] HT-XRPD analysis results confirmed that no conversion of Camp2 to a solid form occurred after exposure to 25°C / 60% RH for 24 months.

[0239] However, at 40°C / 75%RH, a transformation of the solid phase was observed after 3 months. The new powder pattern was named Camp4 powder pattern. More transformation occurred after 24 months, indicating that the camphorsulfonate and free base forms of Form E may be mixed. Fig.30 Shown is the scale-up of Camp 2 and the overlay of the powder patterns after exposure to 25°C / 60%RH and 40°C / 75%RH for 1, 3, 15, and 24 months.

[0240] Fig.31a , Fig.31b The TGA analysis results of Camp2 after exposure to 25°C / 60%RH and 40°C / 75%RH for 1 month are shown. The sample exposed to 25°C / 60%RH for 1 month showed a mass loss of 1.6%, and the sample exposed to 40°C / 75%RH for 1 month showed a mass loss of 1.8%. Both samples thermally decomposed at temperatures above 240°C.

[0241] The Camp2 sample incubated for 3 months at 25°C / 60%RH showed a water content similar to that recorded after 1 month, indicating no significant water absorption under said conditions. However, at 40°C / 75%RH, a transformation from Camp2 to Camp4 solid form was observed. As a result, the TGA analysis results showed a water content of 7.1% (3.3 water molecules per camsylate molecule). The thermal changes recorded in the heat flow signal showed a broad endothermic reaction due to water dissolution, followed by an endothermic reaction due to the melting of the anhydride at a temperature of 150°C (200°C for Camp2).

[0242] The Camp2 sample incubated at 25°C / 60%RH for 15 months showed a water content similar to that recorded after 1 and 3 months, indicating no significant water absorption under the conditions. Camp4 was maintained at 40°C / 75%RH for 15 months. Again, the residual water content was similar to the results after 3 months. TGA analysis of the salt showed a water content of 6.9% (3.3 water molecules per camphorsulfonic acid molecule).

[0243] The heat flow recorded in the heat flow signal shows a broad endothermic reaction due to the dissolution of water, followed by an endothermic reaction due to the melting of the anhydride at a temperature of about 150°C (the melting point of Camp2 is 200°C, so it is different).

[0244] The Camp2 sample incubated at 25°C / 60%RH for 24 months showed a mass loss of 1.9% similar to the mass loss measured at the above time (Figure 34A), indicating no significant water absorption under the conditions described. TGA analysis of the solid obtained after exposure to 40°C / 75%RH for 24 months showed a moisture content of 6.7% (3.2 water molecules per camsylate molecule). The heat flow recorded in the heat flow signal showed a broad endothermic reaction due to the dissolution of water, followed by an endothermic reaction due to the melting of the anhydride at a temperature of about 150°C (the melting point of Camp2 is 200°C, so it is different).

[0245] The chemical purity of the two samples of Camp2 determined by LCMS after exposure to 25°C / 60%RH (Exp. ID GEN50) and 40°C / 75%RH (Exp. ID GEN54) for 1 month was 99.8% ( Fig.35 , Fig.36 ). This indicates that the API is present in the solid phase of Camp2. The chemical purity after 3 months is comparable to that of the 1 month sample ( Fig.37 , Fig.38 ).

[0246] The chemical purity of Camp2 (Exp. ID GEN52) after exposure to 25°C / 60%RH for 15 months was 99.5% ( Fig.39 ), indicating that Camp2 is stable for at least 15 months under the conditions described. The chemical purity of the Camp4 sample (Exp. ID GEN56) after exposure to 40°C / 75%RH for 15 months was 93.7% ( Fig.40 ). This indicates that Camp 2 is converted to Camp 4 at 40°C / 75%RH.

[0247] The chemical purity of Camp2 (Exp. ID GEN53) after exposure to 25°C / 60%RH for 24 months was 100% ( Fig.41 ), which confirms that Camp2 is stable under the conditions described for at least 24 months. The chemical purity of the camphorsulfonate salt after exposure to 40°C / 75%RH for 24 months was 88.6% ( Fig.42 ), which indicates that chemical degradation occurs at 40°C / 75%RH when Camp2 is converted to other forms.

[0248] Camphorsulfonate form of Camp1

[0249] Camp1 was obtained by thermal cycling of small crystalline camphorsulfonate salts obtained after freeze drying. The crystallization solvents for the formation of Camp1 were ethyl acetate, p-xylene and MTBE. The solid phase for further standard positive processes was the salt crystals obtained from MTBE. Camp1 obtained by room temperature drying was exposed to AAC (40°C / 75% RH) for 2 days and was physically stable during vacuum drying ( Fig.43 ).

[0250] The TGA / TGMA analysis results of Camp1 (Figure 44) show that the mass loss between 40 and 200°C is 4.1%, which is mainly caused by water and MTBE according to the MS signal. Thermal decomposition occurs at temperatures above about 240°C, and the heat flow signal shows an endothermic reaction near about 155°C, which is caused by the melting of the anhydride form of the salt.

[0251] TGA / TGMS analysis of a second sample of Camp1 obtained from water showed a mass loss of 3.8% between 25 and 200°C (3.8% corresponds to 1.8 water molecules per camphorsulfonate), which was due to water according to the MS signal. Thermal decomposition was observed at temperatures above about 240°C.

[0252] According to the thermal analysis results of Camp1, Camp1 may be hydrated by water or organic solvent molecules combined on the lattice or a mixture of hydrates / solvates. According to the gradual water loss in the TGA analysis results, Camp1 shows asymmetry because water and organic solvent are located in the channel or exist in the structure in the form of blanks.

[0253] The DSC analysis results of Camp1 obtained from Exp.ID GEN21 showed a broad endothermic reaction from 25℃ to 120℃ ( Fig.46 ), which may be caused by the loss of water and solvent. A gradual endothermic reaction was shown at a temperature of 158.8°C, which was caused by the gradual melting of the anhydride of camphorsulfonate.

[0254] The DSC analysis results of Camp1 obtained from Exp.ID GEN23 showed a broad endothermic reaction from 25℃ to 80℃ ( Fig.47 ), which may be caused by the loss of water. Two endothermic reactions gradually occur between 130 and 180°C, which are caused by the dissolution of water tightly fixed in the crystal lattice of the salt.

[0255] The purity of Camp1 obtained by LCMS was 98.6%, which means that there was API.

[0256] The H-NMR analysis results of Camp1 obtained from Exp.ID GEN21 are shown in Fig.49 This spectrum overlaps with the result of Camp1 obtained from Exp. ID SSm14. From the above similarities, it can be seen that a proton transfer occurred, in this case showing an API:CI ratio of 1:1.

[0257] Crystalline form of Camp2 camphorsulfonate

[0258] Camp2 was the most common form when screening camphorsulfonates, especially in vacuum-dried solids. Mixed forms of Camp4 and Camp2 were detected in several experiments, which was caused by the conversion of Camp2 after exposure to AAC during vacuum drying. In tetrahydrofuran (THF) experiments, Camp5 was found in solids dried at room temperature, which was caused by the conversion of Camp2 during vacuum drying. Table 9 shows the experimental conditions used to generate Camp2. Camp2 was physically stable ( ) when exposed to AAC (40°C / 75%RH) for 2 days. Fig.50 ).

[0259] TGA / TGMS analysis of Camp2 showed a mass loss of 1.7% between 25 and 180°C, which was mainly due to water according to the MS signal (1.7% corresponds to 0.7 water molecules per salt molecule). Thermal decomposition occurred at temperatures above about 240°C, and the heat flow signal showed a significant endothermic reaction around about 200°C, which was caused by the melting of the anhydride form of the salt, followed by decomposition.

[0260] (Table 9): Experimental conditions used to generate Camp2

[0261] Table 14

[0262]

[0263] The DSC analysis results of Camp2 showed a broad endothermic reaction from 25℃ to 70℃ ( Fig.52 ), which may be due to the loss of water. An endothermic reaction occurred at a temperature of 208.9°C, which is related to the melting of the anhydride of the salt.

[0264] The purity of Camp2 determined by LCMS was 97.9% ( Fig.53 ), which indicates that API exists in the solid phase of Camp2.

[0265] Fig.54 H-NMR analysis results for Camp 2 from Exp. ID GEN 17 and Camp 2 from Exp. ID SSm 73 are shown. From the similarity of the spectra it can be seen that a proton transfer has occurred, in this case showing an API:CI ratio of 1:1.

[0266] Crystalline form of Camp4 camphorsulfonate

[0267] Camp4 was obtained by subjecting camphorsulfonate to several thermal cycling experiments. The experimental conditions used to generate Camp4 are shown in Table 10. Camp4 selected for further analysis was obtained from Exp. ID GEN19 (from heptane). Camp4 was physically stable when exposed to AAC (40°C / 75% RH) for 2 days. Fig.55 ).

[0268] The TGA / TGMA analysis results of Camp4 (Figure 56) show that the mass loss between 25 and 200°C is 3.8%, which is mainly caused by water and heptane according to the MS signal. Thermal decomposition occurs at temperatures above about 240°C. The second TGMS analysis results of Camp4 (Figure 57) were obtained from tetrahydrofuran (THF) / water (95 / 5). The TGA / TGMS analysis results show that the mass loss between 40 and 230°C is 9.1%. Among them, 3.2% is caused by water (equivalent to 1.5 water molecules per camphorsulfonate molecule) and 5.9% is caused by tetrahydrofuran (THF) (0.7 tetrahydrofuran molecules). Thermal decomposition is exhibited at temperatures above about 240°C.

[0269] (Table 10): Experimental conditions for the generation of Camp4. lc represents a small amount of crystals. Camp4* is the camphorsulfonate obtained by a crystallization process based on evaporation when no crystalline form appeared after thermal analysis.

[0270] Table 15

[0271]

[0272] DSC analysis results of Camp4 obtained from experiments conducted in heptane ( Fig.58 ) shows a broad endothermic reaction from 25°C to 100°C, which may be caused by the loss of water. An endothermic reaction was recorded at a temperature of 150.4°C, which may be caused by the gradual loss of heptane. No other heat reactions appeared before the thermal decomposition, which indicates that the crystal structure of Camp4 collapsed after the loss of water and solvent.

[0273] The DSC analysis results of Camp4 from the experiments conducted in THF / water (95 / 5) showed a broad endothermic reaction from 25 to 140° C. due to the loss of water. This was followed by a broad endothermic reaction from 160 to 220° C., probably due to the loss of THF. No other thermal reactions occurred between the thermal decompositions.

[0274] The purity of the two Camp4s determined by LCMS was 98.5% and 95.4%, respectively ( Fig.60 , Fig.61 ). This confirms the presence of API in the solid phase of Camp 4. However, some chemical deterioration may occur in the presence of water.

[0275] The H-NMR analysis results of Camp4 obtained from Exp ID GEN19 are shown in Fig.62 The results were similar to those of Camp 2, confirming that proton transfer occurred. The API:CI ratio was calculated to be 1:1.

[0276] The H-NMR analysis results of Camp4 obtained from Exp ID GEN26 are shown in Fig.63 The proton shift was confirmed from the similar results with Camp 2. The API:CI ratio was calculated to be 1:1. An additional resonance shift was confirmed in Camp 4 obtained from GEN 26, which was due to potential impurities according to the HPLC results.

[0277] The present invention is described with reference to the specific embodiments, but it is obvious that various modifications can be made without departing from the technical concept of the present invention. Therefore, it is known that the present invention is not limited to the above embodiments, but also includes the following claims and equivalents.

[0278] Industrial Applicability

[0279] The present invention has industrial applicability.

Claims

1. A camphorsulfonate, characterized in that It is composed of 10-camphorsulfonic acid and a triazolopyrazine derivative represented by the following chemical formula 1: Chemical formula 1:

2. The camphorsulfonate according to claim 1, characterized in that The triazolopyrazine derivative of Chemical Formula 1 is an S-enantiomer.

3. The camphorsulfonate according to claim 2, characterized in that The camphorsulfonate is an optically pure triazolopyrazine derivative of Chemical Formula 1.

4. The camphorsulfonate according to any one of claims 1 to 3, characterized in that The camphorsulfonate is any one of Camp1, Camp2, Camp4, Camp5 and Camp6.

5. The camphorsulfonate according to claim 4, characterized in that The camphorsulfonate is Camp2.

6. The camphorsulfonate according to claim 1, characterized in that The camphorsulfonate salt has a physical stability for at least 2 days at a temperature of 20°C to 50°C and a relative humidity of 35% to 80%.

7. The camphorsulfonate according to claim 1, characterized in that The API purity of the camphorsulfonate salt is at least 95%.

8. The camphorsulfonate according to claim 7, characterized in that The API purity of the camphorsulfonate salt is at least 97.9%.

9. The camphorsulfonate according to claim 1, characterized in that The high-efficiency XRPD spectrum of the camphorsulfonate shows characteristic peaks at 2θ of 14 to 14.5° and 2θ of 16 to 170°.

10. The camphorsulfonate according to claim 1, characterized in that The high-efficiency XRPD spectrum of the camphorsulfonate has the following characteristic peaks: or 11. A method for preparing camphorsulfonate according to claim 1, characterized in that: The preparation method comprises: Step a), adding a compound of the following chemical formula 1 into a reactor containing a solvent; Chemical formula 1: Step b), stirring the compound and the solvent in a reactor; Step c), adding 10-camphorsulfonic acid to the solution in step b); and Step d), cooling the solution of step c) to obtain a precipitate of camphorsulfonate.

12. The method for preparing camphorsulfonate according to claim 11, characterized in that: The solvent includes any one selected from acetonitrile, acetone, 1,2-dimethoxyethane, n-heptane, isopropanol, water or tetrahydrofuran.

13. The method for preparing camphorsulfonate according to claim 12, characterized in that: The 10-camphorsulfonic acid added in step b) is added in an equivalent ratio of 1:0.5 to 1:1.5 relative to the compound of Chemical Formula 1.

14. The method for preparing camphorsulfonate according to claim 13, characterized in that: The equivalent is 1:1.0 to 1:1.2, and the solvent is acetonitrile.

15. The method for preparing camphorsulfonate according to any one of claims 11 to 14, characterized in that: The step b) is performed at a temperature of 45°C to 55°C for at least 1 hour.

16. A pharmaceutical composition, characterized in that The composition comprises the camphorsulfonate according to claim 1 and a pharmaceutically acceptable carrier.

17. The pharmaceutical composition according to claim 16, characterized in that The pharmaceutically acceptable carrier is one or more selected from the group consisting of lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginate, gelatin, calcium silicate, microcrystalline cellulose, polyvinyl pyrrolidone, cellulose, water, syrup, methylcellulose, methyl hydroxybenzoate, propyl hydroxybenzoate, talc, magnesium stearate and mineral oil.

18. The pharmaceutical composition according to claim 17, characterized in that The pharmaceutical composition further comprises at least one selected from the group consisting of a lubricant, a wetting agent, a sweetener, a flavoring agent, an emulsifier, a suspending agent and a preservative.

19. A method for inhibiting the activity of c-Met kinase, characterized in that: The method comprises injecting an effective amount of the camphorsulfonate salt according to claim 1 into the subject.

20. The method for inhibiting the activity of c-Met kinase according to claim 19, characterized in that: The subject exhibits a dysproliferative disorder.

21. The method for inhibiting the activity of c-Met kinase according to claim 20, characterized in that: The abnormal proliferative disease is any one selected from lung cancer, colorectal cancer, pancreatic cancer, rectal cancer, ovarian cancer, renal cell carcinoma, prostate cancer and brain tumor.